The Immediate and Lasting Effects of Heat Waves On Workers - Hannah Klauber; Nicolas Koch; Nico Pestel (Institute of Labor Economics (IZA), 2025)
This paper examines how prolonged exposure to heat affects the labor force's ability to work in the short and long run. Linking administrative public health insurance records for one-third of the German working-age population to the quasi-experimental occurrence of heat waves, we provide the first comprehensive characterization of the occupation-specific heterogeneity in how heat-induced health damages materialize in decreased labor supply, and its distributional implications. An average hot day increases the number of new sick leave cases, and the effects build with prolonged heat. After seven consecutive days of heat exposure, the impact is roughly three times greater than on the first day. Workers who are already disadvantaged in terms of their income and working conditions are more vulnerable to heat stress. Those who are more flexible in scheduling and adjusting their working hours are less at risk. Our results also reveal a longer-term decrease in labor supply in the years following heat wave exposure, and suggest sustained increases in expenditures for healthcare.
Keywords: J20; J32; I18; Q50; 330; heat; labor; inequality; climate change; adaptation